2013
DOI: 10.1371/journal.pone.0080478
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Lung Adenocarcinoma on Cytological Samples Using a Multigene Next Generation Sequencing Panel

Abstract: Identification of driver mutations in lung adenocarcinoma has led to development of targeted agents that are already approved for clinical use or are in clinical trials. Therefore, the number of biomarkers that will be needed to assess is expected to rapidly increase. This calls for the implementation of methods probing the mutational status of multiple genes for inoperable cases, for which limited cytological or bioptic material is available. Cytology specimens from 38 lung adenocarcinomas were subjected to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 42 publications
1
92
0
2
Order By: Relevance
“…Aberrant TGF-β signaling is common in human lung cancer, and loss of SMAD4 is thought to play an important role in the inactivation of TGF-β signaling (38,39). However, the frequency of mutation and/or deletion on SMAD4 is relatively low in NSCLC (40,41); therefore, the actual mechanism of aberrant expression of SMAD4 in NSCLC remained unclear. Given the significant up-regulation of miR-224 in NSCLC and the fact that SMAD4 is a direct target of miR-224, it is possible that loss of SMAD4 might be attributable to up-regulated miR-224 expression in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant TGF-β signaling is common in human lung cancer, and loss of SMAD4 is thought to play an important role in the inactivation of TGF-β signaling (38,39). However, the frequency of mutation and/or deletion on SMAD4 is relatively low in NSCLC (40,41); therefore, the actual mechanism of aberrant expression of SMAD4 in NSCLC remained unclear. Given the significant up-regulation of miR-224 in NSCLC and the fact that SMAD4 is a direct target of miR-224, it is possible that loss of SMAD4 might be attributable to up-regulated miR-224 expression in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Massive parallel sequencing, also known as next-generation sequencing (NGS) or deep sequencing, is the most sensitive approach to index multiple genes even with only a limited amount of DNA from different sources including FFPE tissues [8,9]. NGS can simultaneously investigate multiple potential molecular targets and represents a potent diagnostic complement to histopathological and immunophenotypic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Though, it has been optimized to work with highly fragmented and degraded FFPE DNA, recent studies have shown that it can be used to analyze mutations in cfDNA (https://www.illumina.com/). The Ion Ampliseq Colon and Lung cancer panel on the Ion Torrent Personal Genome Machine selectively amplifies 90 amplicons that encompass 1825 mutational hotspots of 22 genes related to colon and lung cancer [86][87][88]. It has been clinically validated in a retrospective study of 39 NSCLC samples and 51 colorectal cancer samples [84].…”
Section: Methods Targeting Druggable Mutation and Other Aberrations Imentioning
confidence: 99%